2010
DOI: 10.1016/j.jcsr.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Headed steel stud anchors in composite structures, Part I: Shear

Abstract: The Newmark Structural Engineering Laboratory (NSEL) of the Department of Civil and Environmental Engineering at the University of Illinois at Urbana-Champaign has a long history of excellence in research and education that has contributed greatly to the state-of-the-art in civil engineering. Completed in 1967 and extended in 1971, the structural testing area of the laboratory has a versatile strong-floor/wall and a three-story clear height that can be used to carry out a wide range of tests of building materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(63 citation statements)
references
References 16 publications
2
59
0
2
Order By: Relevance
“…8a. Similar to that observed for shear studs [4], the peak strength and ductility of the cyclic specimens are reduced, compared to the corresponding monotonic specimen (i.e., specimen 1-m24-c2-h). This is due to the reduction of the frictional coefficients at the slip planes, which is caused by smoothing of the contact surfaces during cycling, and the release of the bolt pretension, which is caused by the…”
Section: Pushout Testssupporting
confidence: 71%
“…8a. Similar to that observed for shear studs [4], the peak strength and ductility of the cyclic specimens are reduced, compared to the corresponding monotonic specimen (i.e., specimen 1-m24-c2-h). This is due to the reduction of the frictional coefficients at the slip planes, which is caused by smoothing of the contact surfaces during cycling, and the release of the bolt pretension, which is caused by the…”
Section: Pushout Testssupporting
confidence: 71%
“…The application of corresponding resistance factors of 0.75 or tension and 0.65 for shear (Pallarés and Hajjar, 2009) provides safe results for all tests.…”
Section: Chapter 6 Seismic Behavior Of Headed Stud In Tension and Intmentioning
confidence: 98%
“…The assessment of the accuracy of ACI 318-08 and PCI 6th is carried out through the computation of nominal values provided by the standards (using the steel formula and 5% fractile formula for concrete). The nominal shear strength of concrete, , in this work is predicted by pryout failure equations for the corresponding provisions as presented in Pallarés and Hajjar (2009). The nominal tensile strength of concrete, , is predicted by the minimum strength of pull-out and breakout strength presented in this work assuming uncracked concrete.…”
Section: Comparison Of Pcimentioning
confidence: 99%
“…Research work of [14] has investigated on the static and fatigue testing on shear connector using push out tests. Re-cently, [15] have reported a comprehensive compilation of experimental studies on push-out specimens. It is reported that the equations given in [6] need modifications to comply with experimental trends.…”
Section: Introductionmentioning
confidence: 99%